Ադանայի 1909թ. կոտորածների առաջին արձագանքներն արևմտահայ մամուլում - Ղալթախչյան, Տաթևիկ (ՀՀ ԳԱԱ Հայոց ցեղասպանության թանգարան-ինստիտուտ)
The Armenian massacres of April 1909 organized in Adana and surrunding regions were covered intensivly in the Western Armenian press. The media outlets show that the information on the massacres in Adana and neighboring regions, organized by the Hamidian regime, were dominant in the Western Armenian press.
Keywords: Հայոց ցեղասպանություն; Հայոց պատմություն